Analysis of Edu-Tourism Factors among Students in Public Universities in Johor - R. Chandrashekar,; Tey Jo Ann, (Research in Management of Technology and Business, 2021)
Edu-tourism is a tourism activity that merged with education in order to enhance the leisure and experimental learning experience. The sector has been recognized as one of the highly potential source of income for the educational institute and tourism industry. However, a dearth of studies on edu-tourism factors affect the edu-tourism promotion effort significantly. Therefore, the purpose of this study is to identify the major edu-tourism factor and furthermore, forecast the edu-tourists arrivals in 2021. The study was focusing on students who are enrolling in public universities in Johor. The study employed quantitative method and data will be collected by distributing questionnaires to respondents. The data will be analyzed by using Statistical Package for Social Science (SPSS). The study used a validated online survey questionnaire to collect the data from 271 valid respondents. The results showed that the dominant factor that affects edu-tourists travel to Malaysia is the government initiative provided by the destination country and the least chosen is availability of facilities. The government and other related industries should improve the facilities for edu-tourists and maintain the good initiative for them. Based on the data, researcher found that the number of edu-tourist arrivals to Malaysia increase from 26.23 thousand of edu-tourist in 2012 to 30.34 thousand of edu-tourist in 2019. Based on the linear regression equation, the expectant tourist arrivals for 2021 are 28.61 thousand edu-tourists.The results of this study are expected to provide valuable insights to stakeholders and policymakers in the educational and tourism sector.